Empowering Young Minds: The Impact of Philosophy for Children (P4C) and Picture Storybooks on EFL Learners’ Anxiety and Reading Comprehension - Sutono, Agus; Padera, Mark Philip C. (Educalingua Journal, 2025)
This study examines how combining Philosophy for Children (P4C) and picture storybooks can reduce English learning anxiety and improve reading comprehension among Indonesian EFL students. Based on Vygotsky’s sociocultural theory and affective pedagogy, the approach addresses both emotional and cognitive aspects of learning. Using a quasi-experimental mixed-methods design, 121 fourth-semester English Department students were divided into experimental and control groups. The experimental group received lessons that used philosophical dialogue and visual storytelling to encourage critical thinking and emotional involvement. Results showed that this approach significantly lowered students' anxiety and improved their reading comprehension and motivation. Qualitative data also revealed that students felt safer and more engaged, which helped them connect personally with the texts. The study shows that student-centered, interdisciplinary teaching can support both language learning and emotional well-being. It offers useful insights for EFL teachers and curriculum developers aiming to create more meaningful and supportive learning environments.